An evaluation study of a gender-specific smoking cessation program to help Hong Kong Chinese women quit smoking. (December 2015) - Li, Ho; Chan, Sophia; Wan, Zoe; Wang, Man; Lam, Tai
Abstract Background There is a lack of population-based smoking cessation interventions targeting woman smokers in Hong Kong, and in Asia generally. This study aimed to evaluate the effectiveness of a gender-specific smoking cessation program for female smokers in Hong Kong. Methods To evaluate the effectiveness of the service, a total of 457 eligible smokers were recruited. After the baseline questionnaire had been completed, a cessation counseling intervention was given by a trained counselor according to the stage of readiness to quit. Self-reported seven-day point prevalence of abstinence and reduction of cigarette consumption (≥50 %) and self-efficacy in rejecting tobacco were documented at one week and at two, three and six months. Results The 7-day point prevalence quit rate was 28.4 % (130/457), and 21.9 % (100/457) had reduced their cigarette consumption by at least 50 % at the six-month follow-up. The average daily cigarette consumption was reduced from 8.3 at baseline to 6.3 at six months. Moreover, both internal and external stimuli of anti-smoking self-efficacy increased from baseline to six months. Conclusions The study provides some evidence for the effectiveness of the gender-specific smoking cessation program for female smokers. Furthermore, helping smokers to improve their self-efficacy in resisting both internal and external stimuli of tobacco use can be a way of enhancing the effectiveness of a smoking cessation intervention.